2012
DOI: 10.1061/(asce)ir.1943-4774.0000434
|View full text |Cite
|
Sign up to set email alerts
|

Montana Flume Flow Corrections under Submerged Flow

Abstract: A Montana flume is a Parshall flume without a diverging downstream section and is used to measure open channel flow. Under free-flow conditions, the Parshall flume and the Montana flume have the same calibration characteristics, but under submerge flows, their calibrations significantly differ. Tests were conducted at the Utah Water Research Laboratory on an acrylic 15.2-cm (6-in.) Montana flume to determine the effects of submergence on the flow readings. This type of investigation has not been previously ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Ref. [36] studied the Parshall flume and the Montana flume, which have the same calibration procedures under normal free-flow conditions, and tested their calibrations under submerged flows.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…Ref. [36] studied the Parshall flume and the Montana flume, which have the same calibration procedures under normal free-flow conditions, and tested their calibrations under submerged flows.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…Furthermore, eld experiments have shown that the accuracy of this approach is dependent on the submergence ratio (ratio of downstream to upstream depth) (Willeitner et al 2012;Samani 2017;Goel et al 2017). It has been reported that a possible error of up to 60% in the accuracy of umes could occur if the submergence ratio exceeds its limit and ow transitions from free ow to submerged condition.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that a possible error of up to 60% in the accuracy of umes could occur if the submergence ratio exceeds its limit and ow transitions from free ow to submerged condition. (Willeitner et al 2012;Goel et al 2015;Heyrani et al 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation